Limits on anomalous trilinear gauge couplings from WW -> e(+)e(-), WW -> e(+/-)mu(-/+), and WW ->mu(+)mu(-) events from pp collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Soc, 2006)
Limits are set on anomalous WW gamma and WWZ trilinear gauge couplings using W+W--> e(+)nu(e)e(-)(nu) over bar (e), W+W--> e(+/-)nu(e)mu(-/+)nu(mu), and W+W-->mu(+)nu(mu)mu(-)(nu) over bar (mu) events. The data set was collected by the Run II D0 detector at the Fermilab Tevatron Collider and corresponds to approximately 250 pb(-1) of integrated luminosity at root s=1.96 TeV. Under the assumption that the WW gamma couplings are equal to the WWZ couplings and using a form factor scale of Lambda=2.0 TeV, the combined 95% C.L. one-dimensional coupling limits from all three channels are -0.32 <Delta kappa < 0.45 and -0.29 <lambda < 0.30.